2019
DOI: 10.1021/acs.jpclett.9b02570
|View full text |Cite
|
Sign up to set email alerts
|

Ring Polymer Molecular Dynamics in Gas–Surface Reactions: Inclusion of Quantum Effects Made Simple

Abstract: Accurately modeling gas-surface collision dynamics presents a great challenge for theory, especially in the low energy (or temperature) regime where quantum effects are important. Here, a path integral based non-equilibrium ring polymer molecular dynamics (NE-RPMD) approach is adapted to calculate dissociative initial sticking probabilities (S0) of H2 on Cu(111) and D2O on Ni(111), revealing distinct quantum nature in the two benchmark surface reactions. NE-RPMD successfully captures quantum tunneling in H2 di… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(58 citation statements)
references
References 53 publications
1
57
0
Order By: Relevance
“…133,596 There are now numerous instances in which initial-state resolved reaction probabilities computed with QCT have been compared with QD results for a diatomic molecule reacting on a metal surface to assess the accuracy of QCT. Examples include H 2 + Cu(111), 159,597 Ru(0001), 151 Ni(111), 476 Pd(111), 158 Pt(111), 156 Pt(211), 48 and D 2 + Ag (111). 186 Generally, very good agreement is obtained.…”
Section: Ct Methodsmentioning
confidence: 96%
“…133,596 There are now numerous instances in which initial-state resolved reaction probabilities computed with QCT have been compared with QD results for a diatomic molecule reacting on a metal surface to assess the accuracy of QCT. Examples include H 2 + Cu(111), 159,597 Ru(0001), 151 Ni(111), 476 Pd(111), 158 Pt(111), 156 Pt(211), 48 and D 2 + Ag (111). 186 Generally, very good agreement is obtained.…”
Section: Ct Methodsmentioning
confidence: 96%
“…It incorporates ZPE effects and does not suffer from ZPE leakage. [49][50][51] Furthermore, it can incorporate some tunneling effects due to the extension of the ring polymer that can stretch over a barrier and thus lower the effective barrier height. 52 RPMD has been especially successful for the calculations of thermal rate constants in the form of RPMD rate theory.…”
Section: Introductionmentioning
confidence: 99%
“…55 Further numerical tests showed that one can expect similar accuracy of RPMD for calculations with equilibrium and non-equilibrium initial conditions. 55 Very recently, the non-equilibrium initial conditions have been used to obtain microcanonical rate constants from RPMD simulations; 50,57 however, initial state-selectivity could not be addressed in these works.…”
Section: Introductionmentioning
confidence: 99%
“…ZPE effects are incorporated through the harmonic springs connecting the beads, and RPMD therefore respects ZPE constraints and does not suffer from ZPE leakage. [61][62][63] Tunneling effects are also incorporated due to the finite extension of the ring polymer, which can stretch over a barrier and therefore lower its effective height. [54,55,[64][65][66] Originally, RPMD was formulated for the calculation of real-time correlation functions associated with equilibrium initial conditions.…”
mentioning
confidence: 99%
“…[75][76][77] Very recently, the nonequilibrium initial conditions have been used to obtain microcanonical rate constants from RPMD simulations; however, initial state selectivity could not be addressed in these works. [82,62] We have proposed an efficient approach that combines the RPMD approach with QCT simulations to obtain initial state-selective cross sections for bimolecular reactions. [83] Initial state-selective cross sections for the Mu/H/D + H 2 (ν = 0,1) reactions were calculated close to the threshold energy.…”
mentioning
confidence: 99%